Implementasi Model PjBL Berbasis STEM Terhadap Kreativitas Siswa pada Materi Larutan Elektrolit dan Nonelektrolit di MAN Kota Lhokseumawe - Coryna Oktaviani; Agus Muliaman; Evi Listiani (Jurnal Ilmiah Wahana Pendidikan, 2022)
The learning process currently taking place in schools focuses more on improving cognitive aspects, but does not pay more attention to skills aspects, especially student creativity. This study aims to describe students' creativity through the implementation of the PjBL (Project Based Learning) model based on STEM (Science, Technology, Engineering and Mathematics) on electrolyte and non-electrolyte solutions. This research was conducted in MAN Kota Lhokseumawe with sample selection by purposive sampling, namely class X MIA 5 totaling 30 students. This research uses a qualitative approach with descriptive research type. Data were obtained using student creativity assessment sheets. The results showed that the average score of students was 77% with very creative criteria, this was obtained based on the assessments made by the observer in each group. The group is selected heterogeneously, that is, students are grouped based on the mix of their ability to score. The conclusion of the results of this study is that applying the STEM-based PjBL learning model can develop students' creative ideas in the teaching and learning process